THE INFLUENCE OF ONLINE LEARNING ON STUDENT LEARNING OUTCOMES - Norenta Sitohang (Sean Institute, 2023)
Educational technology is an ever-evolving discipline. The development of educational technology is based on the emergence of problems in the teaching and learning process. During the Covid – 19 pandemic, the government made policies related to the teaching and learning process in Higher Education. Where the face-to-face teaching and learning process was abolished and changed to online. The online teaching and learning process aims to break the chain of the spread of the Covid - 19 outbreak. The online teaching and learning process found several problems such as material not fully conveyed and understood, limited quotas for attending lectures online and network access constraints for small areas. These problems trigger the poor learning outcomes obtained. Therefore it is necessary to evaluate the learning process online on student learning outcomes. With the aim of improving the quality of the quality of learning outcomes and also adjustments to learning outcomes. The results of the research testing conducted found that there was no effect of online learning on student learning outcomes. Where the quality of learning outcomes obtained by students is the same as the quality when learning is done face to face.